Pengaruh Peran Orang Tua Terhadap Hasil Belajar Siswa di Desa Laringgi Kabupaten Soppeng - Ritha Tuken; Natriani Syam; Siskariani Siskariani (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2023)
The purpose of this study was to describe the role of parents and student learning outcomes as well as the influence of the role of parents on the learning outcomes of 4th grade elementary school students in Laringgi Village, Soppeng Regency. The independent variable in this study is the role of parents, while the dependent variable is learning outcomes. The study population was all 4th grade elementary school students in the village of Laringgi, Soppeng Regency, totaling 34 people, and 34 people became samples using the total sampling technique. Research data was obtained by distributing questionnaires on the role of parents and learning outcomes data obtained through class teachers. The analysis technique uses simple linear regression and significance test. Based on the results of the descriptive analysis it is known that the role of parents is classified as good with a percentage of 52.9%, and student learning outcomes are classified as good with a percentage of 47.1%. From the results of inferential analysis, the sig. 0.000 <0.05 or H0 is rejected and H1 is accepted which means the role of parents has a positive and significant effect on student learning outcomes.